Genealogy of Islamic Education in Indonesia: Transformation, Innovation, and Challenges - Al Af Ghoni, Achmad Sholakhuddin; Dh, Ahmad Zuhdi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Islamic education in Indonesia has a long-standing history that continues to evolve in response to the dynamics of the times—from mosque- and pesantren-based models to modern formal education systems. These changes are influenced by technological advancements, globalization, and social demands. This study aims to explore the development of the genealogy of Islamic education in the modern era by highlighting its transformations, innovations, and the challenges it faces. The research is conducted through a literature review using historical and analytical approaches.The findings show that Islamic education has undergone significant transformations, such as the digitalization of learning, the integration of competency-based curricula, and the adoption of innovative teaching methods. However, challenges such as unequal access to education, disparities in the use of technology, and efforts to uphold Islamic values remain key concerns. Therefore, a comprehensive strategy is needed to maintain a balance between Islamic traditions and the demands of the digital age, ensuring that Islamic education remains relevant, adaptive, and capable of producing globally competitive generations without losing their Islamic identity.